The use of Think-Talk-Write (TTW) strategy and its effect on the tenth grade students’ ability in writing descriptive text - Rusfandi Rusfandi; Dea Rizky Tamara (Jurnal Inspirasi Pendidikan, 2021)
Common problems that EFL learners face in writing are lack of vocabulary, limited grammar understanding, and idea development. An alternative teaching strategy to help them alleviate these problems is a Think-Talk-Write (TTW) strategy. This study investigates whether the use of the TTW strategy along with audio-visual media gives a positive effect on the students’ descriptive writing ability. Forty-six tenth grade students at a private senior high school participated in this study, and they were divided into experimental and control classes, each consisted of 23 students. The experimental class was taught by using a TTW strategy, and the control class was taught by using a Mind Mapping (MM) strategy. Pre-test and post-test were administered before and after the students received the treatments. The data were analyzed quantitatively. The result of the pre-test shows that there was no statistically different writing score between the two groups of students (t = .58, p > .05). However, a significant difference in scores between the two groups emerged for the post-test (t = 4.42, p < .05). This result suggests that the TTW strategy combined with audio-visual media can be an effective strategy that can be used by English teachers in teaching descriptive writing.